A systematic review of home-based records in maternal and child health for improving informational continuity, health outcomes, and perceived usefulness in low and middle-income countries. - Linju Joseph; Anna Lavis; Sheila Greenfield; Dona Boban; Prinu Jose; Panniyammakal Jeemon; Semira Manaseki-Holland (PLoS ONE)
Background Evidence shows that a gap in the documentation of patients' past medical history leads to errors in, or duplication of, treatment and is a threat to patient safety. Home-based or patient-held records (HBR) are widely used in low and middle-income countries (LMIC) in maternal and childcare. The aim is to systematically review the evidence on HBRs in LMICs for (1) improving informational continuity for providers and women/families across health care visits and facilities, (2) to describe the perceived usefulness by women/families and healthcare providers, and (3) maternal and child health outcomes of using HBRs for maternal and child health care. Methods The protocol was registered in PROSPERO (CRD42019139365). We searched MEDLINE, EMBASE, CINAHL, and Global Index Medicus databases for studies with home-based records from LMICs. Search terms pertained to women or parent-held records and LMICs. Two reviewers assessed studies for inclusion using a priori study selection criteria- studies explaining the use of HBRs in LMIC for maternal and child health care. The included study quality was appraised using the Mixed Methods Appraisal Tool (MMAT). Results from all study designs were summarised narratively. Results In total, 41 papers were included in the review from 4514 potential studies. Included studies represented various study designs and 16 countries. The least evaluated function of HBR was information continuity across health care facilities (n = 6). Overall, there were limited data on the usefulness of HBRs to providers and mothers/families. Home-based records were mostly available for providers during health care visits. However, the documentation in HBRs varied. The use of HBRs is likely to lead to improved antenatal visits and immunisation uptake, and skilled birth delivery in some settings. Mothers' knowledge of breastfeeding practices and danger signs in pregnancy improved with the use of HBRs. One randomised trial found the use of HBRs reduced the risk of cognitive development delay in children and another reported on trial lessened the risk of underweight and stunted growth in children. Conclusion There is limited literature from LMICs on the usefulness of HBRs and for improving information transfer across healthcare facilities, or their use by women at home. Current HBRs from LMICs are sub-optimally documented leading to poor informational availability that defeats the point of them as a source of information for future providers.